Suprachiasmatic nucleus in a patient with multiple system atrophy with abnormal circadian rhythm of arginine-vasopressin secretion into plasma - Ozawa, Tetsutaro; Oyanagi, Kiyomitsu; Tanaka, Hajime; Horikawa, Yoh; Takahashi, Hitoshi; Morita, Takashi; Tsuji, Shoji (Journal of the neurological sciences, 1998)
We performed a quantitative investigation of arginine-vasopressin (AVP) immunopositive neurons in the suprachiasmatic nucleus (SCN), which is the endogenous clock of the brain of a patient with multiple system atrophy (MSA) who exhibited nocturnal polyuria associated with decreased urinary specific gravity and depression of nocturnal AVP secretion. Eleven age- and sex-matched subjects were used as controls. Although, the number of AVP-positive neurons was decreased in neither the supraoptic nucleus nor the paraventricular nucleus, the number of AVP-positive neurons in the SCN was decreased and gliosis was present in the SCN. The cytoplasmic area of AVP-immunopositive neurons in the SCN was smaller in the patient than in the control subjects. These findings raise the possibility that SCN is involved in MSA and the neurodegeneration in the SCN results in altered circadian rhythm of AVP secretion and nocturnal polyuria.